Impact of degenerative radiographic abnormalities and vertebral fractures on spinal bone density of women with osteoporosis - Costa-Paiva, Lúcia; Pinto-Neto, Aarão Mendes; Filardi, Silvana; Samara, Adil; Marques Neto, João Francisco (São Paulo Medical Journal, 2002)
CONTEXT: Measurements of bone density taken by dual-energy x-ray absorptiometry are the most accurate procedure for the diagnosis of osteoporosis.Thisprocedurehasthedisadvantage ofmeasuringthedensityofallmineralcomponents, includingosteophytes,vascularandextravertebral calcifications. These alterations can influence bone density results and densitometryinterpretation. OBJECTIVE: To correlate radiography and densitometry findingsfromwomenwithosteoporosis,analyzing the influence of degenerative processes and vertebralfracturesontheevaluationofbonedensity. DESIGN: Retrospective study. SETTING: Osteoporosis outpatients’ clinic at Hospital das Clínicas, Universidade Estadual de Campinas. PARTICIPANTS: Ninety-six postmenopausal women presenting osteoporosis diagnosed by bone density. MAIN MEASUREMENTS: Bone mineral density of the lumbarspineandfemoralneckweremeasuredby thetechniqueofdual-energyx-rayabsorptiometry, using a LUNAR-DPX densitometer. Fractures, osteophytesandaorticcalcificationswereevaluated by simple x-rays of the thoracic and lumbar spine. RESULTS: The x-rays confirmed vertebral fractures in 41.6%, osteophytes in 33.3% and calcifications of the aorta in 30.2%. The prevalence of fractures and aortic calcifications increased with age. The mean bone mineral density was 0.783g/cm2 and the mean T-score was –3.47 DP. Neither fractures nor aortic calcifications had significant influence on bone mineral density (P = 0.36 and P = 0.09, respectively),despitethefracturedvertebraehaving greater bone mineral density (P < 0.02). Patients withlumbarspineosteophytesshowedgreaterbone mineral density (P = 0.04). Osteophytosis was associatedwithlumbarspinebonemineraldensity afteradjustmentforfracturesandaorticcalcifications by multiple regression (P = 0.01). CONCLUSION: Osteophytes and lumbar spine fractures can overestimate bone density interpretation. The interpretation of densitometry results should be carried out together with the interpretation of a simple lumbar spine x-ray in elderlywomen.